Pretending to be authentic: challenges for students when reflective writing about their childhood for assessment. Issue 3 (4th May 2018) - Newcomb, Michelle; Burton, Judith; Edwards, Niki
Abstract: Critical reflection potentially allows social work and human service (SWHS) students to understand how past experiences can shape their future practice. This study of 20 Australian undergraduate SWHS students with a history of childhood adversity found reflective writing for this purpose was not a useful pedagogical practice. Rather than developing skills in critical reflection students found the task performative, linked to academic requirements, where they needed to display emotional containment. Consequently, SWHS academics need to examine reflective writing about childhood adversity for assessment as this process may not enable students to build skills in critical reflection that drive professional development.